A Comparison of the Effects of Epidural Analgesia Versus Traditional Pain Management on Outcomes After Gastric Cancer Resection: A Population-Based Study. Issue 3 (1st May 2014) - Cummings, Kenneth C.; Patel, Meatal; Htoo, Phyo Than; Bakaki, Paul M.; Cummings, Linda C.; Koroukian, Siran
Abstract : Background and Objectives: Epidural analgesia may increase survival after cancer surgery by reducing recurrence. This population-based study compared survival and treated recurrence after gastric cancer resection between patients receiving epidurals and those who did not. Methods: We used the linked federal Surveillance, Epidemiology, and End Results Program/Medicare database to identify patients aged 66 years or older with nonmetastatic gastric carcinoma diagnosed 1996 to 2005 who underwent resection. Exclusions included diagnosis at autopsy, no Medicare Part B, familial cancer syndrome, emergency surgery, and laparoscopic procedures. Epidurals were identified by Current Procedural Terminology codes. Treated recurrence was defined as chemotherapy greater than or equal to 16 months and/or radiation greater than or equal to 12 months after surgery. Recurrence was compared by conditional logistic regression. Survival was compared via marginal Cox proportional hazards regression model. Results: We identified 2745 patients, 766 of whom had epidural codes. Patients receiving epidurals were more likely to have regional disease, be white, and live in areas with relatively high socioeconomic status. Overall treated recurrence was 25.6% (27.5% epidural and 24.9% nonepidural). In the adjusted logistic regression, there was no difference in recurrence (odds ratio, 1.40; 95% confidence interval [CI], 0.96–2.05). Median survival did not differ: 28.1 months (95% CI, 24.8–32.3) in the epidural versus 27.4 months (95% CI, 24.8–30.0) in the nonepidural groups. The marginal Cox models showed no association between epidural use and mortality (adjusted hazard ratio, 0.93; 95% CI, 0.84–1.03). Conclusions: There was no difference between groups regarding treated recurrence or survival. Whether this is true or simply a result of insufficient power is unclear. Prospective studies are needed to provide stronger evidence.